The Performance of Chenin blanc Grafted onto Different Rootstock Cultivars on a Dundee Soil in the Montagu District - Southey, J.M.; Fouche, G.W. (South African Journal of Enology and Viticulture, 2017)
The performance of Chenin blanc grafted onto 15 different rootstock cultivars and clones, established on a sandy alluvial soil in the Montagu district, was investigated. Over the eleven years of the trial, the highest mean yields were obtained with 99 Richter (Clone: RY 13), Constantia Metallica, Dog Ridge, Ramsey and 101-14 Mgt. The mean yield of99 Richter (Clone: RY 13) was significantly higher than that of the other 99 Richter clones and selections. The highest pruning masses were found with 143-B Mgt, Dog Ridge, Constantia Metallica and Ramsey. The crop-to-pruning-mass ratio of 143-B Mgt was, however, lower than that of the other graft combinations, which suggests that this graft combination was undercropped and that potentially higher yields could have been obtained. Moderate growth was obtained with the cultivars 101-14 Mgt and 3306 Coucerc. These cultivars showed potential as growth-limiting cultivars as they consistently produced relatively high yields with satisfactory grape composition, associated with low pruning masses.